Structural fire design of load-bearing cold-formed steel assemblies from a prototype metal building. (July 2022) - Yan, Xia; Gernay, Thomas
Abstract: This paper describes a procedure to complete the structural fire design of cold-formed steel structures and applies it to column assemblies taken from a prototype one-story metal building designed following U.S. building codes. The fire design procedure includes the definition of performance objectives, design fires, heat transfer analyses by the finite element method, and structural analyses using both the Direct Strength Method and finite element modeling. The results show that the design by analysis achieves the required performance while enabling flexibility and efficiency in design. Thermal analyses provide steel temperatures consistent with prescriptive fire ratings and are also used to demonstrate adequacy of unrated assemblies such as protected double C-shaped sections. The finite element model confirms the applicability of the Direct Strength Method with appropriate retention factors to evaluate the elevated temperature response. The cold-formed steel columns maintain stability well beyond their prescriptive rating owing to the low applied load resulting from the ASCE/SEI 7 load combination in the fire situation, which does not include wind. Therefore, for structures which are lightly loaded in the fire situation, such as these metal building columns, analysis methods can be used to demonstrate superior performance compared to the applied fire resistance rating.